Water Resource Development and its Influence on Eco-environment in the Mainstream of Tarim River, China - Zu, Ruiping; Cheng, Gipdpmg; Gao, Qianzhan (Annals of Arid Zone, 2016)
This paper outlines the influence of water resource development on the hydrological conditions and ecology of the mainstream of the Tarim River basin during last 50 years. Due to large-scale reclamation in the upper reaches, the discharge in the lower reaches decreased significantly, many terminal lakes dried up, and the water quality is getting worse. Such hydrological changes have resulted in seriously .. environmental degradations, such as soil salinization, vegetation degeneration and desertification and so on. In addition, the "Green Corridor" in lower reaches fading away gradually, and the Taklimakan Desert and the Kurmtag Desert are closing up to each other. In order to protect the environment and maintain sustainable development in the region, a holistic planning should be put forward and carried out timely. It should take into consideration the interests of the upper, middle and lower reaches, distribute and use the water resources rationally, and coordinate the relationship between economic development and environmental protection.